Pisando tierra podcast - Centeno Laurente, María José (2019)
Pisando Tierra is a podcast that comments sustainability issues in order to explain the seventeen Sustainable Development Goals (SDGs) promoted by the United Nations (UN) as part of the global goals that all 193 countries that conform this organization should reach towards the 2030 Agenda. We made this product with the motivation to raise awareness of the SDGs. In addition, we highlight peruvian initiatives that currently contribute to this global goal from different work areas, and we try to communicate all these information in a simple way. After interviewing experts about the content published in Pisando Tierra, we improved the proposal of the podcast. For doing so, the statistics obtained from Spotify, the main platform for the reproduction of Pisando Tierra, and Anchor, an audio storage platform, were analyzed. During the project, the content of the podcast was shared through two social networks, aligned with the interests of the project's target audience.